Maternal Nutritional Knowledge and its Association with Iron Deficiency Anemia in Children - Ismail, Ameera; Fatima , Fahima (Nurture, 2017)
This study aimed at assessing the maternal nutritional knowledge and determining the association between nutritional knowledge and Hb status of their children. A total of 143 children of 2 – 10 years was selected for this study from local community. Data was collected using questionnaire for maternal nutritional knowledge and portable hemoglobinometer for identifying hemoglobin status of children. SPSS version 22 was used for data entry and analysis. Among the mothers who had poor nutritional knowledge (7.69%) all the children were anaemic. Even among mothers with average knowledge (63.64%) a vast majority of children were anaemic (86.8%). Among mothers with high nutritional knowledge (28.67%) more than half (58.5%) children were anaemic. Relationship between maternal nutrition knowledge and hemoglobin level of children was statistically significant (p<0.001). The results showed a very high rate of anaemia and a significant association between maternal knowledge and Hemoglobin status of their children, as proved by many studies.